Mobilizing resources with an investment case to mitigate cross-border malaria transmission and achieve malaria elimination in South Africa - Aparna Kollipara; Devanand Moonasar; Ryleen Balawanth; Sheetal P. Silal; Anthony Yuen; Katie Fox; Joseph Njau; Yogan G. Pillay; Mark Blecher (Global Health Action, 2023)
South Africa’s effort to eliminate malaria is significantly challenged by a large number of imported malaria cases, especially from neighbouring Mozambique. The country has a funding gap to achieve its malaria elimination goals (prior to 2019) and is ineligible to receive a national allocation from the Global Fund. The findings of an IC were utilised to successfully mobilise resources for malaria elimination in South Africa in 2018. A five-step resource mobilisation strategy was implemented to highlight financing challenges and leverage the economic evidence from an IC for malaria elimination in South Africa. South Africa’s malaria programme implements control and elimination activities in three malaria-endemic provinces (KwaZulu Natal, Limpopo, and Mpumalanga). Driven by the IC findings, the South African government took an unprecedented step and increased total domestic malaria financing by approximately 36%, from the 2018/19 to the 2019/20 financial years through the creation of a new conditional grant for malaria. The IC findings predicted that malaria control in southern Mozambique is a prerequisite to eliminate malaria in South Africa. Based on this, the South African government also allocated funding towards a co-financing mechanism to support malaria control efforts in southern Mozambique. The IC findings assisted the South African National Department of Health to make a convincing case to key government decision-makers to invest in national malaria elimination and maximise economic returns in the long run. The South African government is the first in Southern Africa to mobilise a significant increase in domestic malaria financing to address the financial sustainability of both national and regional malaria elimination efforts. Continued surveillance activities will be required to prevent the re-establishment of malaria transmission even after malaria elimination is achieved in South Africa. Information sharing and close collaboration with provincial and national government officials were key to the successful outcome.